Mengatasi Kemunduran Akhlak Pemuda Di Zaman Modern Melalui Analisis Kisah Teladan Nabi Yusuf Dalam Surah Yusuf - Alexa Ayu Dewanda; Hanestesia Zahara; Resya Eka Putri; Wismanto (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
Currently, life in Indonesia is very advanced, so human resources must always be updated in accordance with natural science, technology, social and morals. There is a lot of research related to the aim of overcoming the moral decline of young people in this era but it has not yet comprehensively revealed the aim of the research. This research aims to describe an analysis of how to overcome the moral decline of young people in modern times using the story of the Prophet Yusuf AS. according to Yusuf's letter. The method in this research uses a qualitative method based on library research. This research is a type of research that focuses on library analysis. This researcher used library sources to obtain research materials, the main data in this research came from books, magazines and the latest journal articles related to the theme of this research. The results of this research indicate that the objectives of research on the moral decline of modern youth are (1) the moral decline of today's young generation, (2) the story of the Prophet Yusuf in the Koran, and (3) language that contains the moral values of the Prophet Yusuf AS. in the story.